Naive, captive long-tailed macaques (Macaca fascicularis fascicularis) fail to individually and socially learn pound-hammering, a tool-use behaviour - Elisa Bandini; Claudio Tennie (Royal Society Open Science, 2018)
A subspecies of long-tailed macaques (Macaca fascicularis aurea; Mfa) has been reported to use stone tools and a specific technique to process nuts in Southeast Asia, a behaviour known as ‘pound-hammering’. The aim of this study was to examine the development of pound-hammering in long-tailed macaques: whether this behavioural form can be individually learnt or whether it has to rely on some forms of social learning. Given the absence of Mfa from captivity, long-tailed macaques of a highly related subspecies (Macaca fascicularis fascicularis; Mff) were experimentally tested by providing them with the ecological materials necessary to show pound-hammering. A baseline was first carried out to observe whether pound-hammering would emerge spontaneously without social information. As this was not the case, different degrees of social information, culminating in a full demonstration of the behaviour, were provided. None of the subjects (n = 31) showed pound-hammering in any of the individual or social learning conditions. Although these data do not support the hypothesis that individual learning underlies this behaviour, no evidence was found that (at least) Mff learn pound-hammering socially either. We propose that other—potentially interacting—factors may determine whether this behaviour emerges in the various subspecies of long-tailed macaques, and provide a novel methodology to test the role of social and individual learning in the development of animal tool-use.